The Body as an Electronic Scheme - Strakhova, O. P.; Страхова, Оксана Петрівна (My University, 2024)
There is no clear evidence that acupuncture points and meridians are separate organs or specific tissues. However, in traditional Chinese medicine, the mechanism of acupuncture action is associated with the vital energy concept. To identify the body’s energy source and the material basis of its transmission, transformation, and use, it is necessary to consider it as an energy-generating object, with all its components. By abstracting from the body’s usual structural view, we found that it is an autonomous energy-generating object. The human body generates energy through the lungs and digestive tract, which are electrochemical generator organs. Because the generated energy must be transferred to the consumer, the body has wire and transformer analogs. It bears an obvious resemblance with an electronic circuit, where cellular structures, tissues, and their combinations act as electrical and radioelements. The heart, brain, and muscles, which have well-known electrical parameters, as well as acupuncture points, offer information about the state of these electronic circuits. This article describes an extra-organ approach for systematizing body structures. It also attempts to represent the meridians and acupuncture points system as integral electro-radioelements, as well as the local circuit components of the whole body’s electronic scheme.
https://orcid.org/0000-0002-9188-6833
Keywords: Acupuncture points; Acupuncture meridians; Energy system of the organism